2023
DOI: 10.1017/jfm.2023.212
|View full text |Cite
|
Sign up to set email alerts
|

Post-shock turbulence recovery in oblique-shock/turbulent boundary layer interaction flows

Abstract: The oblique shock impinging on the supersonic turbulent boundary layer leads to a mixing layer and the emergence of large-scale coherent structures within the interaction zone which leave significant velocity defect and turbulence amplification downstream. In the present study, we investigate the turbulence recovery in the post-shock region by exploiting direct numerical simulation data of the oblique-shock/turbulent boundary layer interaction flow at the incoming Mach number of $2.28$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…This is probably due to two counteracting effects: one is the increment of the friction Reynolds number in the streamwise direction (figure 3), and the other is the weakening of the VLSMs, similar to the observations in the recovery downstream of the shock/TBL interactions (Yu et al. 2023).…”
Section: Local Turbulence Statisticssupporting
confidence: 77%
See 3 more Smart Citations
“…This is probably due to two counteracting effects: one is the increment of the friction Reynolds number in the streamwise direction (figure 3), and the other is the weakening of the VLSMs, similar to the observations in the recovery downstream of the shock/TBL interactions (Yu et al. 2023).…”
Section: Local Turbulence Statisticssupporting
confidence: 77%
“…In the study of Yu et al. (2023) that discussed the negative during the turbulence recovery downstream of the shock/TBL interactions, incompatible growth rates were found between the nominal and kinetic energy thicknesses, with the former much higher than the latter, suggesting that the kinetic energy dissipation per unit length is lowered. This is also the case for the presently considered TBL in the WSP and its neighbourhood (omitted for brevity), in that the ratio between the kinetic energy thickness and the nominal thickness is lower as it approaches downstream.…”
Section: Local Turbulence Statisticsmentioning
confidence: 97%
See 2 more Smart Citations
“…Li et al (2019) extended this method to compressible flow and investigated the influence of density and viscosity on the skin friction of the supersonic turbulent channel and zero-pressure-gradient turbulent boundary layers (Fan, Li & Pirozzoli 2019). Yu et al (2023) performed DNS of impinging SWTBLIs at Mach 2.28 and applied the RD method to analyse the generation mechanism of C f . Their results indicated that, in the upstream boundary layer, C f was mainly contributed by mean viscous dissipation and TKE production; as the flow entered the interaction zone, the contribution from the advection term was also significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%